A comparative review on adsorption and photocatalytic degradation of classified dyes with metal/non-metal-based modification of graphitic carbon nitride nanocomposites: Synthesis, mechanism, and affecting parameters - Ahmadi, Abbas; Hajilou, Mersad; Zavari, Saman; Yaghmaei, Soheila (Journal of cleaner production, 2023)
Dyes have different categories, and each is used in one of the industries according to its appearance and physical characteristics. Dyes have severe toxicity and carcinogenic effects, which in water effluents contaminates the aquatic system and threatens other parts of the ecosystem and humans. Dye removal using absorption and photocatalytic properties has been the subject of various fundamental researches. Graphitic carbon nitride (g-C3N4) as a photocatalyst is a good choice because of its many excellent features, like adjustable optical band gap and excellent chemical and thermal stability. Although this catalyst has great potential to eliminate contamination, its use is limited because of the low separation of excited carriers. Therefore, modifying the existing graphitic carbon nitride photocatalyst is necessary to improve its properties and overcome the drawbacks. Considering the number of published experimental papers, connecting with other semiconductors and doping metal/non-metal materials is one of the most popular solutions that has shown remarkable results so far. In this study, after an overview and classification of dyes, the review paper investigates the synthesis, interface, and modification of graphitic carbon nitride nanomaterials, affecting parameters and mechanism of both photocatalytic degradation and adsorption removal of categorized dyes. Experimental work on fabricating the pure, binary, and tertiary graphitic carbon nitride nanocomposite was discussed. Photocatalytic process parameters like light source, pH, temperature, dissolved oxygen, initial concentration, catalyst content, stability and recycling of these materials have been analyzed. This paper could be helpful for researchers focusing on the synthesis of carbon graphite nitride, its composites, and their photocatalytic activity. It could also be a resource for understanding the type of dyes and their environmental effects. [Display omitted] •Dyes were categorized and classified into different group based on their chemical structures and applications.•The role of adsorption mechanism and its synergic effect on photocatalytic process were studied.•Different synthesis methods of g-C3N4 and its metal/nonmetal and plasmonic modification were investigated.•Stability and reusability of g-C3N4-based nanomaterials towards degradation of dyes are described.•Operating conditions effects, pH, temperature, dye concentration, and catalyst content were reviewed.